'Life' and education policy: intervention, augmentation and computation. Issue 2 (4th March 2018) - Gulson, Kalervo N.; Webb, P. Taylor
ABSTRACT: In this paper, we are interested in the notion of multiple ways of thinking, knowing and transforming life, namely an increasing capacity to intervene in 'life' as a 'molecular biopolitics', and the changing ways in which 'life' can be understood computationally. We identify and speculate on the ways different ideas of life, drawing from humanities, social, life and computing sciences, may impact the ways we think about and know education policy. We focus on key aspects of education policy around self-responsibilisation and choice, new forms of network governance and the move to education data science. The paper examines what is required to understand how advancements in the life and computing sciences may be implemented within educational institutions and organisations, and what political and ethical issues might pertain to the challenges these new advancements bring to educational institutions.